The Impact of COVID-19 on People’s Access to Healthcare and Health Behavior in a Sample of Indian Population: A Cross-Sectional Study - Dandge , Shailendra; Kanumuri, Manisha; Eppalapally, Akhil Kumar (International Journal of Medical Students, 2023)
Background: The threat of COVID-19 is likely to have contributed to changes in people's behavior related to accessing healthcare, modifying lifestyles, and exploring alternative methods of securing health. The objectives, therefore, were to characterize the challenges in accessing healthcare, and the countermeasures that people adopted to mitigate such challenges. Methods: A cross-sectional survey was conducted using a 26-item questionnaire on google forms. It was administered to individuals 18 years and older. The participants were family members of medical students at MediCiti Institute of Medical Sciences, Hyderabad, India. Continuous data are summarized as mean and standard deviation, while categorical data are represented in proportions and percentages. Data analysis was done using STATA Version 14.2. Results: Of the expected 600 participants, 247 responded (41.7% response rate), and nearly 63% reported difficulties in accessing healthcare during the lockdown. About 40% of the participants reported that they visited a hospital for non-COVID-19 health concerns. However, none of them felt comfortable with the hospital visit for the risk of acquiring COVID-19 infection. Similarly, nearly 62% of those with chronic illnesses defaulted on their regular follow-up visits. Further, nearly 50% reported taking unprescribed medications or supplements, and about 65% reported adopting preventive measures such as steam inhalation or diet modification. Nearly 50% expressed that given an option, they would not prefer online consultations. Conclusion: The majority of participants reported difficulties in accessing healthcare during the lockdown and subsequent unlock phases. Self-medication with multivitamins, use of home remedies, and traditional and alternative forms of medicine were high. However, the preference for online consultations was low.